Evaluation of Risk Attitude of Rice Farmers in Kwara State, Nigeria - Ayinde, O.E.; Bello, K.A.; Ajewole, O. O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2016)
Risk is synonymous with agriculture especially rice production which is a major staple food in Nigeria. Attitude of rice farmers to risk taking is an important factor to be considered in productive activities. The present study evaluates risk attitude of rice farmers in Kwara State using 3-stage random sampling techniques to select 120 rice farmers. Descriptive statisitics as well as analytical techniques namely Cobb-Douglas production function and Tobit regression were employed as tools of analysis. The result showed that 46.7% of the respondents are experienced in rice farming, while 68.3% of the respondents engage in other profitable enterprise apart from farming. The result of the risk attitude showed that rice farmers are risk averse (86.0%) based on the selected determinants of risk aversion including household size, rice output, total asset and total farm income. It is therefore recommended that policy makers should put into consideration risk attitude of farmers and effort should be made to increase farmers’ asset and income.